From 'Sophisticated' to 'Garbage': An Exploration of Qualitative Barriers in the School Educational Technology Infrastructure Maintenance and Procurement Cycle - Ulfatul Munawaroh; Sayidah Eva Milatul Qistiyah; Nur Anim Jauhariyah (ICO EDUSHA, 2025)
This study aims to explore the qualitative barriers to infrastructure maintenance and the educational technology procurement cycle in schools, which can lead to devices that were once "sophisticated" becoming "digital waste." Using a descriptive qualitative approach, this study explores real-world conditions through interviews, observations, and analysis of school documents. The study results showed that device failures occurred more quickly due to the lack of maintenance SOPs, a limited maintenance schedule, and weak damage reporting mechanisms. During the procurement stage, schools focused more on sophistication and budget absorption than on analyzing pedagogical needs, resulting in many devices not being appropriate for the learning context. Teachers' low digital literacy hampered the optimal use of technology, while the lack of an inventory system resulted in ineffective planning for device maintenance and replacement. This study concluded that the root of the problem lies in unintegrated technology management, including maintenance, procurement, competency development, and curriculum planning. These findings are expected to encourage schools to develop more systematic and sustainable technology lifecycle management so that devices can have a real impact on learning.